Incomplete information about social preferences explains equal division and delay in bargaining - Stefan Kohler (Games, 2012)
Two deviations of alternating-offer bargaining behavior from economic theory are observed together, yet have been studied separately. Players who could secure themselves a large surplus share if bargainers were purely self-interested incompletely exploit their advantage. Delay in agreement occurs even if all experimentally controlled information is common knowledge. This paper rationalizes both regularities coherently by modeling heterogeneous social preferences, either self-interest or envy, of one bargaining party as private information in a three period game of bargaining and preference screening and signaling.
Keywords: D03; D81; C73; 330; alternating-offer bargaining; asymmetric information; envy; fairness; inequality aversion; uncertainty